Species of the genus Abuta (Anomospermeae, Menispermaceae) from Peru - Ortiz, Rosa del C. (2025)
The genus Abuta constitutes the second most diverse taxon within the Neotropical Menispermaceae. In this research, we document and analyze 12 species recorded within Peruvian territory, presenting comprehensive morphological characterizations of each taxon and compiling these into a dichotomous identification key. We provide photographic documentation of specimens, encompassing both in situ observations and herbarium specimens, for all species with the exception of A. aristeguietae. This study incorporates detailed analyses of geographic distributions at both national and global scales for each species. A significant methodological constraint has been encountered in the limited availability of fertile specimens, which are frequently restricted to a single sex (either staminate or pistillate specimens), thereby presenting substantial challenges for interspecific comparative analyses. While Abuta grandifolia emerges as the most widely distributed and frequently collected species, recent investigations indicate that this taxon likely represents a complex of distinct entities whose taxonomic boundaries remain to be fully elucidated.